2017
DOI: 10.3892/etm.2017.4398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biological characteristics of nucleus pulposus mesenchymal stem cells derived from non-degenerative and degenerative human nucleus pulposus

Abstract: Abstract. Cell therapy using mesenchymal stem cells provides a promising approach for the treatment of intervertebral disc degeneration (IDD). In recent years, human nucleus pulposus mesenchymal stem cells (NPMSCs) have been identified in nucleus pulposus tissue and displayed great potential for the regeneration of IDD. However, biological differences between non-degenerative and degenerative nucleus pulposus-derived NPMSCs have remained to be defined. The aim of the present study was to compare the biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…Compared to the colony-forming cells isolated from the healthy NP tissues, these cells from the early degenerated NP tissues formed less colonies and proliferated slower. A recent study showed similar results when comparing the stem cells isolated from human degenerated NP tissues with those from healthy ones [ 40 ]. The T2 signal intensity of MRI showed the worsening degeneration of the punctured discs with the extension of time in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Compared to the colony-forming cells isolated from the healthy NP tissues, these cells from the early degenerated NP tissues formed less colonies and proliferated slower. A recent study showed similar results when comparing the stem cells isolated from human degenerated NP tissues with those from healthy ones [ 40 ]. The T2 signal intensity of MRI showed the worsening degeneration of the punctured discs with the extension of time in this study.…”
Section: Discussionmentioning
confidence: 66%
“…cd29 is an anchorage protein involved in cell adhesion and migration, and its expression indicates cell populations with a higher migratory capacity (22). Although the low intensity of cd105 expression was reported by Blanco et al (13), this result was different from previous reports, which demonstrated that MSc-like cells from degenerated NP tissues displayed a MSc marker profile that was highly positive for CD73, CD90, CD105, cd44, cd56 and cd146, and negative for cd45 (23,24). This may be attributed to a different quality of the NP tissues obtained from surgical specimens.…”
Section: Discussionmentioning
confidence: 86%
“…The expression of NP-specific progenitor marker and NP cell marker Tie2, also referred to as cd202b, is a cellular membrane receptor tyrosine kinase of the Tie family (23). Tie2 has been identified as a marker of NP precursor cells that were found to exhibit multipotency and self-renewal capacity in animal and human NP (23,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, endogenous MSCs stimulation and recruitment is indicated to be an essential way to repair IVD degeneration [5]. Previous studies have confirmed that human degenerated and normal IVD contained human nucleus pulposusderived mesenchymal stem cells (hNP-MSCs) [6][7][8][9] and hNP-MSCs fulfilled morphological, immunophenotypic, and differentiation definition criteria described by the International Society of Cell Therapy for mesenchymal stromal cells. These cells could retard the process of IVD degeneration [10].…”
Section: Introductionmentioning
confidence: 99%